Modelo para a gestão ambiental da cadeia de suprimentos: análise das empresas de linha branca - Brassolatti, Tatiane Fernandes Zambrano (2009)
The objective of this thesis is to propose a model for the environmental supply chain management of the appliance industry. This model was proposed from the analysis of the literature on the main models for the GCS and for the GACS and through a research in five appliance industries and in four first level suppliers of these industries. It was used the case study as the research methodology. The literature review about GACS showed that existing models that prioritize some aspects to the detriment of others, does not refer to GACS as a whole, focusing only on isolated concepts. Moreover, the research showed that the practice of the appliance industries do not follow a model for the GACS. Thus, it s necessary to propose a model for the environmental supply chain management of the appliance industry. The model implementation may be a way to integrate the key links in the supply chain of the appliance industry. This integration occurs through the establishment of a coordinator agent that leads to the environmental management. Other important components of the model are: the method of coordination in the chain, the definition of common environmental policy and goals for all organizations in the chain, the lifting of legal and consumer requirements, the recommendations for each process of the companies and the preparation of plans improvement. The research also sought to obtain a practical evaluation of the proposed model by this thesis in the studied companies. Overall, the model for the GACS was well evaluated and all respondents consider this important issue, although no actions have been reported to promote the GACS.